2012
DOI: 10.1016/j.physa.2011.10.020
|View full text |Cite
|
Sign up to set email alerts
|

How people make friends in social networking sites—A microscopic perspective

Abstract: We study the detailed growth of a social networking site with full temporal information by examining the creation process of each friendship relation that can collectively lead to the macroscopic properties of the network. We first study the reciprocal behavior of users, and find that link requests are quickly responded to and that the distribution of reciprocation intervals decays in an exponential form. The degrees of inviters/accepters are slightly negatively correlative with reciprocation time. In addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This has also been called the rich get richer effect. Some authors have suggested to distinguish between preferential creation and preferential reception in directed networks (Hu & Wang, 2012;Mislove, Koppula, Gummadi, Druschel, & Bhattacharjee, 2008;J. Zhao, Lui, Towsley, Guan, & Zhou, 2011).…”
Section: Theoretical Background Factors Determining Friendship Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been called the rich get richer effect. Some authors have suggested to distinguish between preferential creation and preferential reception in directed networks (Hu & Wang, 2012;Mislove, Koppula, Gummadi, Druschel, & Bhattacharjee, 2008;J. Zhao, Lui, Towsley, Guan, & Zhou, 2011).…”
Section: Theoretical Background Factors Determining Friendship Formationmentioning
confidence: 99%
“…Researchers who have distinguished preferential creation from preferential reception have usually only used in-degree (i.e., sent invitations) to predict creation and out-degree (received invitations) to predict reception (Mislove et al, 2008; S. Zhao, 2006) or found that out-degree is the better predictor of preferential reception (Hu & Wang, 2012). However, there is also a theoretical reason to expect that the number of received friendship requests is the more important predictor; it is the cue with a higher warranting value, that is, a cue that is more difficult to manipulate (Walther & Parks, 2002).…”
Section: The Present Researchmentioning
confidence: 99%
“…The results of the research are also helpful for understanding the behavior of people on social media. There have been some studies that have shown that the behavior reported in the past research in sociology is also observed on social media [7,12,6,15]. One of such studies on the behavior of people has proposed the concept of triadic closure for explaining how people behave when they connect to each other.…”
Section: Related Workmentioning
confidence: 99%
“…As a special type of social networking sites [1][2][3], online dating sites have emerged as popular platforms for single people to seek potential romance. According to a recent survey, nearly 40 million single people (out of 54 million) in the U.S. have been trying online dating, and about 20% of committed relationships began online [4].…”
Section: Introductionmentioning
confidence: 99%